2021
DOI: 10.2196/23088
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Game for Young Adolescents to Improve Parental Communication and Prevent Unintended Pregnancy and Sexually Transmitted Infections (The Secret of Seven Stones): Development and Feasibility Study

Abstract: Background Early adolescent unintended pregnancy and sexually transmitted infection prevention are significant public health challenges in the United States. Parental influence can help adolescents make responsible and informed sexual health decisions toward delayed sexual debut; yet parents often feel ill equipped to communicate about sex-related topics. Intergenerational games offer a potential strategy to provide life skills training to young adolescents (aged 11-14 years) while engaging them an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…SSS [ 25 ] is a web-based adventure game for teenagers aged 11 to 14 years in the United States aimed at education to prevent unwanted pregnancy and sexually transmitted infections. SSS emphasizes educational training to acquire knowledge about sex-related topics and is based on an intervention mapping approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SSS [ 25 ] is a web-based adventure game for teenagers aged 11 to 14 years in the United States aimed at education to prevent unwanted pregnancy and sexually transmitted infections. SSS emphasizes educational training to acquire knowledge about sex-related topics and is based on an intervention mapping approach.…”
Section: Resultsmentioning
confidence: 99%
“…The results provided preliminary support for the hypotheses that playing an avatar-based virtual reality technology game would strengthen peer resistance skills and that early adolescent Hispanic girls would have a positive response to this game. SSS [25] is a web-based adventure game for teenagers aged 11 to 14 years in the United States aimed at education to prevent unwanted pregnancy and sexually transmitted infections. SSS emphasizes educational training to acquire knowledge about sex-related topics and is based on an intervention mapping approach.…”
Section: Serious Games Studies With Significant Resultsmentioning
confidence: 99%
“…A total of 18 studies identified within the systematic review were included in the synthesis on effectiveness and user experiences investigated in primary studies related to serious games in STI prevention ( Table 2 ). Three of the studies are usability tests that focus on usability, user experience, and cultural adaptation or adaptation, among other factors [ 30 - 32 ]. One of these studies only reported perceived efficacy [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four of these 7 studies additionally integrated the question whether the participants were willing to repeat the serious game [ 30 , 33 , 38 , 47 ], where 3 of them found that a majority of participants were willing to do so [ 30 , 38 , 47 ]. Three out of the 10 studies addressed the aspect of motivation in general [ 32 , 39 , 41 ]. One study assessed motivation using questions in the domains of attention, relevance, confidence, and satisfaction related to the serious game, showing increased motivation among intervention participants [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 18 studies identified within the systematic review were included in the synthesis on effectiveness and user experiences investigated in primary studies related to serious games in STI prevention (Table 2). Three of the studies are usability tests that focus on usability, user experience, and cultural adaptation or adaptation, among other factors [30][31][32]. One of these studies only reported perceived efficacy [31].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%